Pengaruh Perbedaan Komitmen Organisasi Ditinjau Dari Gender Terhadap Turnover Labour Pada Ud. Klinik Laptop Paiton - Nur Najmi Jazila; Afi Rahmat Slamet; Muhammad Ridwan Basalama (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to explain the effect and differences of Organizational Commitment in terms of Gender on Turnover Labor at UD. Clinic Laptop Paiton. This research uses associative research and quantitative methods. With all  the population are employees of UD. Klinik Laptop Paiton. With a sample size of 30 respondents using a saturated sampling technique or census. The analysis method used is simple linear regression analysis and different test. The collecting method of data uses a questionnaire with the research result shows that organizational commitment in terms of gender has an effect on Turnover Labor at UD. Klinik Laptop Paiton. And there is no difference in organizational commitment in terms of gender at UD. Klinik Laptop Paiton.Keywords: Organizational Commitment, Gender, Turnover Labor